The great risk shift?: income volatility in an international perspective - Claudia M. Buch (Center for Economic Studies and ifo Institute (CESifo), 2008)
Weakening bargaining power of unions and the increasing integration of the world economy may affect the volatility of capital and labor incomes. This paper documents and explains changes in income volatility. Using a theoretical framework which builds distribution risk into a real business cycle model, hypotheses on the determinants of the relative volatility of capital and labor are derived. The model is tested using industry-level data. The data cover 11 industrialized countries, 22 manufacturing and services industries, and a maximum of 35 years. The paper has four main findings. First, the unconditional volatility of labor and capital incomes has declined, reflecting the decline in macroeconomic volatility. Second, the idiosyncratic component of income volatility has hardly changed over time. Third, crosssectional heterogeneity in the evolution of relative income volatilities is substantial. If anything, the labor incomes of high- and low-skilled workers have become more volatile in relative terms. Fourth, income volatility is related to variables measuring the bargaining power of workers. Trade openness has no significant impact.
Keywords: E32; E25; 330; Income volatility; distribution risk; real business cycles